Quantification of thermal dose in moderate clinical hyperthermia with radiotherapy: a relook using temperature–time area under the curve (AUC). (1st January 2021) - Datta, Niloy R.; Marder, Dietmar; Datta, Sneha; Meister, Andreas; Puric, Emsad; Stutz, Emanuel; Rogers, Susanne; Eberle, Brigitte; Timm, Olaf; Staruch, Michal; Riesterer, Oliver; Bodis, Stephan
Abstract: Background: Thermal dose in clinical hyperthermia reported as cumulative equivalent minutes (CEM) at 43 °C (CEM43) and its variants are based on direct thermal cytotoxicity assuming Arrhenius 'break' at 43 °C. An alternative method centered on the actual time–temperature plot during each hyperthermia session and its prognostic feasibility is explored. Methods and materials: Patients with bladder cancer treated with weekly deep hyperthermia followed by radiotherapy were evaluated. From intravesical temperature (T) recordings obtained every 10 secs, the area under the curve (AUC) was computed for each session for T > 37 °C (AUC > 37 °C) and T ≥ 39 °C (AUC ≥ 39 °C). These along with CEM43, CEM43(>37 °C), CEM43(≥39 °C), T mean, T min and T max were evaluated for bladder tumor control. Results: Seventy-four hyperthermia sessions were delivered in 18 patients (median: 4 sessions/patient). Two patients failed in the bladder. For both individual and summated hyperthermia sessions, the T mean, CEM43, CEM43(>37 °C), CEM43(≥39 °C), AUC > 37 °C and AUC ≥ 39 °C were significantly lower in patients who had a local relapse. Individual AUC ≥ 39 °C for patients with/without local bladder failure were 105.9 ± 58.3 °C-min and 177.9 ± 58.0 °C-min, respectively ( p = 0.01). Corresponding summated AUC ≥ 39 °C were 423.7 ± 27.8 °C-min vs. 734.1 ± 194.6 °C-min ( p < 0.001), respectively. The median AUC ≥ 39 °C for each hyperthermia session in patients with bladder tumor control was 190 °C-min. Conclusion: AUC ≥ 39 °C for each hyperthermia session represents the cumulative time–temperature distribution at clinically defined moderate hyperthermia in the range of 39 °C to 45 °C. It is a simple, mathematically computable parameter without any prior assumptions and appears to predict treatment outcome as evident from this study. However, its predictive ability as a thermal dose parameter merits further evaluation in a larger patient cohort.